Examination of the Factors Impacting the Interest of Residents in Semarang City in Mobile Health Applications: An UTAUT Analysis - Perdana, Muhamad Putra; Abidin, Zaenal (Scientific Journal of Informatics, 2024)
Purpose: The study aims is to examine the determinants that impact the level of public interest in utilizing mobile health (m-health) applications in Semarang City, Indonesia. Our specific objective is to identify the critical factors that facilitate or impede the public's adoption of these applications.Methods: This study objective was pursued using a comprehensive approach. A study model was developed utilizing the Unified Theory of Acceptance and Use of Technology (UTAUT) as its foundation. This model encompasses essential variables including performance expectancy, effort expectancy, social influence, facilitating conditions, price value, and perceived trust. The process of data collecting was carried out by means of a survey that was disseminated across widely used social media channels. The study was conducted using a sample size of 257 participants who are residents of Semarang City. The data that was collected underwent a thorough analysis utilizing the Partial Least Squares - Structural Equation Model (PLS-SEM) approach.Results: The research conducted in our study resulted in several significant findings. The study revealed that several factors, namely performance expectancy, social influence, price value, and perceived trust, had a notable and beneficial impact on users' inclination towards using m-health applications. On the other hand, the variables of effort expectancy and facilitating conditions did not exhibit a statistically significant influence on the level of public interest in these applications. Furthermore, a substantial correlation was found between the behavioral intention and the actual usage behavior of inhabitants of Semarang City in their adoption of m-health applications.Novelty: The research presented in this study is distinguished by its comprehensive analysis of the various factors that impact the adoption of mobile health (m-health) applications in Semarang City. Through the incorporation and expansion of variables such as price value and perceived trust, our study provides a comprehensive and nuanced comprehension of this particular occurrence by adapting and extending the UTAUT model. Our work emphasizes the importance of performance expectancy and social influence, while also suggesting the need for additional investigation into the roles of effort expectancy and facilitating conditions. Additionally, our study offers valuable information regarding the influence of age and gender as moderators in these associations. The results of this study have significant practical implications for healthcare professionals and policymakers who are interested in promoting the use of mobile health (m-health) technologies among the public. Additionally, these findings can serve as a valuable guide for future research endeavors in this particular area of study.